1989
DOI: 10.1021/j100349a061
|View full text |Cite
|
Sign up to set email alerts
|

Glass-liquid transition and the enthalpy of devitrification of annealed vapor-deposited amorphous solid water: a comparison with hyperquenched glassy water

Abstract: The thermal behavior of vapor-deposited amorphous solid water (ASW) was investigated by differential scanning calorimetry.After annealing in vacuo, ASW shows a thermally reversible glass-liquid transition: the onset temperature is 136 ± 1 K, the temperature range of the transition is ~14 deg, and the increase in the heat capacity is 1.9 ± 0.2 J K'1 mol™1. The heat of crystallization of the annealed ASW to cubic ice is -1.29 ± 0.01 kJ mol'1. These values are similar to those previously reported for hyperquenche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
222
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(241 citation statements)
references
References 0 publications
16
222
3
Order By: Relevance
“…In particular, as it was shown by an earlier study of thermal evolution of the hyperquenched water droplets by using X-ray diffraction and differential calorimetry, an ice phase predominantly in the form of vitreous ice could be obtained at deposition temperature below 140 K. 6 It should be noted that the temperatures for glass-to-liquid transition and for crystallization to Ic are found to be 129-143 K and 165 K, respectively. 6,51 The temperature of crystallization of amorphous ice to Ic is generally a function of the deposition temperature and postdeposition history of the amorphous sample, which reflects the complex heterogeneous nature of amorphous ice. 52 Furthermore, the thermal evolution data for hyperquenched solid water prepared at 130-150 K 6 suggests the formation of a mixture of cubic ice and glassy materials.…”
Section: Noncrystalline Ice Deposition At 128-145 Kmentioning
confidence: 99%
“…In particular, as it was shown by an earlier study of thermal evolution of the hyperquenched water droplets by using X-ray diffraction and differential calorimetry, an ice phase predominantly in the form of vitreous ice could be obtained at deposition temperature below 140 K. 6 It should be noted that the temperatures for glass-to-liquid transition and for crystallization to Ic are found to be 129-143 K and 165 K, respectively. 6,51 The temperature of crystallization of amorphous ice to Ic is generally a function of the deposition temperature and postdeposition history of the amorphous sample, which reflects the complex heterogeneous nature of amorphous ice. 52 Furthermore, the thermal evolution data for hyperquenched solid water prepared at 130-150 K 6 suggests the formation of a mixture of cubic ice and glassy materials.…”
Section: Noncrystalline Ice Deposition At 128-145 Kmentioning
confidence: 99%
“…The mechanisms responsible for these morphology changes are not fully understood, particularly at low temperature, where diffusion of molecules is limited (Garrod et al 2008). In previous studies a collapse of pores has also been concluded following X-ray and electron diffraction studies (Hallbrucker et al 1989;Jenniskens et al 1995), temperature-programmed desorption (Collings et al 2003), infrared spectroscopy (Hagen et al 1983;, internal friction (Hessinger et al 1996) and gas adsorption experiments (Bar-Nun et al 1998;Kimmel et al 2001;Horimoto et al 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Here we report results of heat capacity C p and thermal conductivity, in situ, measurements, which are consistent with a reversible transition from annealed HDA to ultraviscous high-density liquid water at 1 GPa and 140 K. On heating of HDA, the C p increases abruptly by ð3.4 AE 0.2Þ J mol −1 K −1 before crystallization starts at ð153 AE 1Þ K. This is larger than the C p rise at the glass to liquid transition of annealed ASW at 1 atm, which suggests the existence of liquid water under these extreme conditions. glass transition | pressure-induced amorphization | relaxation U nlike most liquids that vitrify by normal supercooling, water vitrifies only by hyperquenching of its micron-size droplets, and its porous amorphous state is made by vapor deposition (1)(2)(3). Pure bulk water densified by high pressure also does not vitrify on normal cooling; instead it freezes to proton-disordered high-density ices.…”
mentioning
confidence: 99%